Bovine spongiform encephalopathy risk management in Latin America: Costa Rica as a representative country for risk management and policy - Wilson, Margaret A. (2010)
Costa Rica is a representative Latin American country with significant regional cattle production for its size. The country experienced an exceedingly low challenge for bovine spongiform encephalopathy (BSE) as evidenced by no direct meat and bone meal imports from the UK, few imported cattle, no specified risk materials imports from high risk countries, and cattle that are entirely grass-fed. In addition, there is little domestic feed recycling or potential for amplification and the country has further improved its tracing of imported cattle. Risk management to control both internal and external BSE risk factors has been implemented in Costa Rica, and it has negligible risk for domestic BSE. Costa Rica has complied with World Organisation for Animal Health (OIE) surveillance standards. To date Costa Rica has not reported any cases of either BSE or variant Creutzfeldt-Jakob disease (vCJD).